Another DRAM involved in autophagy and cell death - Mrschtik, Michaela (Autophagy, 2016)
Macroautophagy (hereafter referred to as autophagy) is controlled by a number of core proteins that are critical for all autophagy responses. In addition, a number of autophagy regulators have been found that are not critical for macroautophagy per se, but which play roles in regulating autophagy in either selective situations or in response to specific stimuli. In a recent study, we reported the initial characterization of a new autophagy regulator encoded by TMEM150B that is related to the Damage-Regulated Autophagy Modulator, DRAM1. We have termed this factor DRAM3 for DRAM-Related/Associated Member 3. Interestingly, like DRAM1, DRAM3 regulates both autophagy and cell death, but we found these two functions of the protein are not intrinsically connected.